The Role of Technology in the Development of Critical Thinking: Systematic Literature Review - Fitriani, Rizka; Prodjosantoso, AK (Postgraduate, University of Mataram, 2024)
The role of technology in developing critical thinking skills in students. Technology helps create an interactive, collaborative learning environment and supports independent learning. This systematic study aims to investigate the influence of the use of technology, including mobile-based applications, educational games, and e-learning platforms, on the development of critical thinking skills in chemistry learning through the investigation process of articles published and indexed in Scopus. Systematic Review Method: (1) Formulate review questions, (2) Establish inclusion and exclusion criteria, (3) Develop search strategies for search strategies and find studies, (4) Select studies, (5) Extract data, (6) Assess the quality of studies, (7) Analyze and interpret the results. Articles found in the Google Scholar database, the Journal of Turkish Science Education and Scopus show that there are 15 articles that meet the inclusion criteria. The conclusion obtained is to affirm that the integration of technology in the educational process has great potential to develop critical thinking skills.